Elotuzumab Enhances CD16-Independent NK Cell-Mediated Cytotoxicity against Myeloma Cells by Upregulating Several NK Cell-Enhancing Genes - Yan-Hua Wang; Shotaro Hagiwara; Hiroshi Kazama; Yuki Iizuka; Norina Tanaka; Junji Tanaka (Journal of Immunology Research)
Multiple myeloma (MM) is an intractable hematological malignancy caused by abnormalities in plasma cells. Combination therapy using antibodies and natural killer (NK) effectors, which are innate immune cells with safe and potent antitumor activity, is a promising approach for cancer immunotherapy and can enhance antitumor effects. Elotuzumab (Elo) is an immune-stimulatory antibody that targets the signaling lymphocytic activation molecule family 7 (SLAMF7) expressed on the surface of MM and NK cells. We confirmed that Elo strongly promoted NK cell-mediated antibody-dependent cellular cytotoxicity (ADCC) against SLAMF7-positive MM cells in a CD16-dependent NK cell line, and also activated expanded NK cells derived from peripheral blood mononuclear cells of healthy donors and patients with MM in the present study. However, the antitumor effects and genes involved in the direct promotion of NK cell-mediated activation using Elo in CD16-independent NK cells are not clearly known. In this study, we demonstrated that Elo pretreatment significantly enhanced CD16-independent NK cell-mediated cytotoxicity in both SLAMF7-positive MM.1S and SLAMF7-negative K562, U266, and RPMI 8226 tumor cells. Upon direct simulation of CD16-independent NK cells with Elo, increased levels of CD107a degranulation and IFN-γ secretion were observed along with the upregulation of granzyme B, TNF-α, and IL-1α gene expression. The enhanced NK cell function could also be attributed to the increased expression of the transcription factors T-BET and EOMES. Furthermore, the augmentation of the antitumor effects of CD16-independent NK cells upon pretreatment with Elo enhanced the expression of CRTAM, TNFRSF9, EAT-2, and FOXP3 genes and reduced the expression of HSPA6. Our results suggest that Elo directly promotes the cytotoxic function of CD16-independent NK cells against target cells, which is associated with the upregulation of the expression of several NK cell-enhancing genes.